Studi Revitalisasi Fasilitas Ruang Tunggu Terminal Penumpang Domestik Bandar Udara Internasional El Tari Kupang Pasca Badai Seroja - Atmaja, Rika Ardhy; Puspitasari, Yulia Aji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Facilities at the airport are divided into two main parts consisting of the land side and the air side. Existing facilities on the land side consist of: passenger terminal, cargo terminal, operational building, air traffic control tower or Air Traffic Control (ATC), SAR (Search and Rescue) building, meteorological building, main/VIP class building, entrance , fueling building, as well as administrative and office buildings. While the facilities on the air side consist of: runways, taxiways, aircraft parking areas, runway strips or runway end safety areas, as well as aviation accident rescue and fire fighting facilities. This research uses a type of qualitative research and descriptive research type. The purpose of the authors using qualitative research is to describe and reveal the facts and symptoms contained in the research problem, namely to analyze and describe the revitalization of the waiting room for the domestic passenger terminal at El Tari Kupang International Airport.The strategy for repairing damaged and unfit for use due to the Seroja storm has been realized and the damaged and unfit for use facilities have received proper and prompt treatment due to good coordination and cooperation between operating units and related units that were damaged. In addition, efforts to maintain. The quality of facilities is an important thing to prioritize because it has a high level of importance, but in practice there are still many complaints from service users who feel unsatisfied regarding the quality of the facilities available at El Tari Kupang International Airport, especially in the waiting room. Keywords: security,waiting room, and comfortness.